Chemistry the molecular nature of matter and change - Silberberg, Martin S. (Boston : McGraw-Hill, 2000)
Keys to study of chemistry; The components of matter. Stoichiometry; The major classes of chemical reactions. Gases and kinetic-molecular theory; Thermochemistry. Quantum theory and atomic structure; Electron configuration and chemical periodicity; Models of chemical bonding; The shapes of molecules. Theories of covalent bonding...,.
Keywords: Chemistry; Chemistry